PERFORMANCE OF BALITBANGTAN'S UGGUL KAMPUNG CHICKEN (KUB) GIVEN DRAGON FRUIT EXTRACT(Hylocereus polyrhizus) THROUGH DRINKING WATER - L.M.P., Tambak; Siti, N. W.; Wibawa, A. A.P.P. (Jurnal Peternakan Tropika; Vol 12 No 4 (2024): Vol. 12 No. 4 Tahun 2024; July - August, 2024)
This study aims to determine the effect of giving dragon fruit peel extract through drinking water on the performance of Balitbangtan superior native chickens (KUB). This research was conducted for 8 weeks. The design used was a completely randomized design (CRD) with 4 treatments and 4 replications. Each replicate used 5 KUB chickens aged 1 week with homogeneous body weight so that 16 experimental units were obtained with a total of 80 KUB chickens used. The four treatments were dragon fruit peel extract level in drinking water 0%, 3%, 6% and 9% for P0, P1, P2 and P3, respectively. The variables observed were initial and final body weight, total ration consumption, total drinking water consumption, body weight gain, and feed conversion ratio (FCR). The results showed that the final body weight and body weight gain and feed conversion ratio (FCR) in P3 were significantly different (P<0.05) higher than the P0 treatment, while ration consumption and drinking water consumption were not significantly different (P<0.05) higher than P0. Based on the results of this study, it can be concluded that the provision of dragon fruit peel extract at the level of 9% is able to produce the highest final body weight and weight gain as well as the lowest feed conversion ratio (FCR) in Balitbangtan superior native chickens (KUB).